A Real-Time and Low Power Working Method for Mobile WSN. (7th July 2014) - Du, Xiaotong; Zhang, Wei; Li, Dong
Abstract : In many mobile wireless sensor network (WSN) applications, the low power problem is often ignored to maintain the real-time property of monitoring nodes. To solve the long-time working problems of mobile nodes and the whole WSN network, this paper provides a new working method. First, the real-time and consumption features are compared between the Random Mechanism (RM) and Time-Division Mechanism (TDM) through experiments. Secondly, a mobile Time-Division Mechanism based on subnet node ID is designed to reduce the power consumption on the premise of real-time requirements effectively. At the same time, relevant experimental results demonstrate that time synchronization mechanism cannot improve the real-time performance effectively.